Velocities of warm galactic outflows from synthetic Hα observations of star-forming galaxies - Ceverino, Daniel; Arribas, Santiago; Colina, Luis; Rodríguez Del Pino, Bruno; Dekel, Avishai; Primack, Joel (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. The velocity structure imprinted in the Hα emission line profiles contains valuable information about galactic outflows. Using a set of high-resoluti
In original form 2015 November 24
Gesehen am 29.04.2020